(untitled) (Bangladesh Journal of Otorhinolaryngology, 2026)
Background: Supraglottic laryngeal carcinoma presents a significant risk for cervical lymph node metastases, which significantly influences prognosis and treatment planning. Knowledge of the pattern and frequency of nodal involvement is essential for appropriate clinical management. To determine the frequency, pattern, and characteristics of cervical lymph node involvement in individuals with supraglottic laryngeal carcinoma. Methods: This cross-sectional study at Mymensingh Medical College (July 2024–May 2025) included 40 patients with supraglottic squamous cell carcinoma. Diagnosis and tumor assessment were done via history, ENT exam, laryngoscopy, imaging, and biopsy. Data were analyzed descriptively. Approval of ethical standards and consent from participantswere obtained, maintaining confidentiality. Results: Cervical lymph node metastasis was present in 40% of patients, most frequently affecting Level II (50%) and Level III (37.5%) nodes. Nodal involvement was predominantly homolateral (87.5%), with N1 disease being the most common stage (62.5%). Bilateral involvement was observed in 12.5% of cases. The majority of patients exhibited early tointermediate stage disease, and well-differentiated squamous cell carcinoma was the predominant histological type (57.5%). Conclusion: Cervical lymph node metastasis occurs commonly in supraglottic carcinoma, with early-stage, homolateral nodal involvement predominating. Careful assessment of cervical nodes, particularly Levels II and III, is crucial for optimal management. Bangladesh J Otorhinolaryngol 2025; 31(2): 77-85